College openings and local economic development - Berlingieri, Francesco; Gathmann, Christina; Quinckhardt, Matthias (Discussion paper, 2022)
We study how the presence of a college affects the local economy using administrative data. Our analysis exploits the opening of new institutions of tertiary education across Germany in the 1980s and 1990s. The new college substantially increased the student population and share of high-skilled workers in the region. Yet, we find no effect on regional wages or employment indicating that the local economies did not experience additional growth through skill-biased technological change, for instance. Instead, there is sizable heterogeneity in the local gains: high-tech firms in manufacturing absorb most of the new college graduates, esp. in engineering professions. We find little impact on the low- or high-skilled service sector or employment in managerial professions. Finally, we show that local labor market conditions prior to the opening matter: in regions with a more dynamic labor market, the opening encourages firm creation and a permanent upskilling of the workforce. Areas with a less dynamic labor market experience little sustained growth in high-skilled workers who are absorbed by incumbent firms.
Keywords: Graue Literatur